Employment effects of acquisitions: Evidence from acquired European firms - Harald Oberhofer (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper examines the employment effects of acquisitions for acquired European firms taking non-random selection of acquisition targets explicitly into account. Following the empirical firm growth literature and theories put forward in the mergers and acquisition (M&A) literature we control for convergence dynamics in firm size and distinguish between different types of acquisitions. Empirically, we estimate an endogenous treatment model using accounting data for a newly created sample of acquired and non-acquired European firms. Our results reveal positive employment effects for all different types of acquisitions.
Keywords: C21; G34; L22; L25; 330; Acquisitions; employment effects; firm growth; endogenous treatment model